Implementation of Cooperative Learning Strategies to Improve the Speaking Skills in the Islamic School Insan Cendikia Payakumbuh: ØªØ·Ø¨ÙŠÙ‚ Ù†Ù…ÙˆØ°Ø¬ Ø§Ù„ØªØ¹Ù„Ù… Ø§Ù„ØªØ¹Ø§ÙˆÙ†ÙŠ Ù„ØªØØ³ÙŠÙ† Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù… ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø¥Ù†Ø³Ø§Ù† Ø¬Ù†Ø¯ÙŠÙƒÙŠØ§ Ø§Ù„Ø¹Ø§Ù„ÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø¨Ø§ÙŠØ§ÙƒÙ…Ø¨ÙˆÙ‡ - Rizka Widayanti (Universitas Yudharta Pasuruan, 2022)
The study aims to examine the use of cooperative learning strategies to enhance speaking skills in an Islamic school. The research uses a qualitative approach and case study method, data is collected through interviews, observation, and documents. The participants are the head of the institute, teachers, and students. The objectives are to understand the planning, demonstrate the implementation and evaluate the effectiveness of the cooperative learning strategies used. The study found that the planning of the cooperative learning strategies to improve speaking skills included preparing teachers, dividing students into small groups of mixed abilities, and implementing daily activities, group discussions and dialogue practices. The evaluation found that the strategies were effective, resulting in improved speaking skills and increased social skills for the students, particularly for female students who emphasized vocabulary memorization and served as cooperative learning models.